Patterns in the Multiannual Course of Growing Season in Central Europe Since the End of the 19th Century - Szyga-Pluta Katarzyna; Tomczyk Arkadiusz M.; Piotrowicz Katarzyna; Bednorz Ewa (Quaestiones Geographicae, 2022)
The research identified patterns in the multiannual course of start and end dates, and length of growing season (GS) in Central Europe since the end of the 19th century in selected cities of Central Europe in the period 1893–2020. GS start in the analysed stations was characterised by high year-to-year variability, particularly in those located more southwards, i.e. in Prague and Vienna. A smaller variability occurred in GS end dates. The GS was subject to prolongation, although these changes in particular cities were uneven and had different causes. In Toruń and Potsdam, its increase was caused by a greater shift of the end date, and in the remaining stations, it was determined by its earlier start date. Two subperiods were distinguished that differ in terms of intensity of changes of the start and end dates, as well as the length of the GS. The intensification was observed recently.